2021
DOI: 10.1002/anie.202012995
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Prion‐Mimic Foldamer to Induce Controlled Protein Aggregation

Abstract: Proteins reconfigure their 3D‐structure, and consequently their function, under the control of specific molecular interactions that sense, process and transmit information from the surrounding environment. When this fundamental process is hampered, many pathologies occur as in the case of protein misfolding diseases. In this work, we follow the early steps of α‐synuclein (aS) aggregation, a process associated with Parkinson's disease etiopathogenesis, that is promptly promoted by a light‐mediated binding betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…[41,42] To this end, more diverse peptides with different lengths, amino acid sequences and their structural and functional modulations will be tested. In addition, hydrazone-peptide hybrids for guest recognitions, catalytic reactions, [55] functional self-assembly [68][69][70] will also be explored in due course.…”
Section: Discussionmentioning
confidence: 99%
“…[41,42] To this end, more diverse peptides with different lengths, amino acid sequences and their structural and functional modulations will be tested. In addition, hydrazone-peptide hybrids for guest recognitions, catalytic reactions, [55] functional self-assembly [68][69][70] will also be explored in due course.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of chemical space can be conveniently tuned in foldamers, an essential property for the optimization of interactions with targets. Various foldamers, including Oligoquinoline (OQ)-based and photoresponsive prion-mimics have been shown to modulate the self-assembly of islet amyloid polypeptide 22 26 , Aβ peptide 21 , and αS 27 whose aggregation is associated with type 2 diabetes (T2D),Alzheimer’s disease (AD), and PD respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that Aaa (Δ Z βAla) residue in a peptide allows formation of an N-H••O = C intra-residue H-bond which closes a 6-membered pseudo ring system, allowing the peptide to form a well-de ned 3D architecture of the attened β sheet 29 . Recent studies demonstrated that foldamers containing Δ Z βAla/Δ E βAla units display interesting conformational, electronic, and supramolecular aggregation properties that can be modulated by selective E-Z photoisomerization [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%